Nurses' opinions on euthanasia in Spain: an evaluation using a new version of the EAS - Daniel Lerma-García; María Laura Parra-Fernández; Cristina Romero-Blanco; María Soledad Olmo-Mora; María Dolores Onieva-Zafra (BMC, 2024)
Abstract Background Bioethical dilemmas at the end of life have led to regularization processes for the provision of medical assistance in dying patients in different countries. Since the regulation of euthanasia in Spain in 2021, the euthanasia act has been included as one of the benefits of the health system, which has undergone uneven development and implementation in different autonomous communities. The aim of this study was to review the Spanish version of the Euthanasia Attitude Scale following the partial modification of four items. Methods A cross-sectional study was conducted with a non-probabilistic sample of Spanish health workers from Islas Baleares. A self-reported sociodemographic questionnaire and the Euthanasia Attitude Scale were used for data collection. The psychometric properties of the scale were assessed, including reliability and validity, using a confirmatory factor analysis and a parallel analysis. Results The Cronbach's alpha of the EAS was α = 0.892, which implies good internal consistency. According to the confirmatory factor analysis, a Kaiser-Meyer-Olkin-value of 0.938 was obtained, and the result of Bartlett's test of sphericity was < 0.001. The questionnaire included four loading factors, which explained up to 56.99% of the variance. The parallel analysis revealed three significant factors and a fourth, less interpretative factor. Conclusions The EAS-ES-R is a valid instrument for assessing the attitudes toward euthanasia of both trainees and practicing health professionals. It may also be of vital importance in detecting training, support and implementation needs for laws regulating euthanasia in Spain.